Tunable electromagnetic properties of Ti3C2Tx/rGO foams decorated with NiO particles. Issue 33 (5th August 2022) - Zhang, Fan; Shang, Siyang; Li, Yaya; Fan, Bingbing; Zhang, Rui; Zhao, Biao; Lu, Hongxia; Ma, Chengliang
Abstract : Ti3 C2 T x MXene-based composites are attractive for using as the electromagnetic wave absorption (EMA) materials due to the multiple polarizations. Abstract : Ti3 C2 T x MXene-based composites are attractive for use as electromagnetic wave absorption (EMA) materials due to their high conductivity and abundant dipoles on the surface. Nevertheless, the controlled synthesis of MXene foams with tailored dielectric properties for high-performance microwave absorption is still a challenge. Herein, the porous structure of MXene foams has been realized through a freeze–thaw assembly strategy in the presence of reduced graphene oxide (rGO). By adjusting the amounts of magnetic units of NiO particles, the complex permittivity and permeability of MXene/rGO can be tuned. The developed uniform cellular structure enables multiple reflections and scattering of electromagnetic waves among the microcellular network while the cooperation of NiO particles generated through calcination contributes to dielectric loss and magnetic loss. The obtained Ti3 C2 T x /rGO/NiO composites achieve a minimal reflection loss of −62.98 dB at 7.5 GHz. This work provides a promising strategy for designing light weight and multifunctional MXene foam-based microwave absorbers.